Depression and Quality of Life in Older Gay and Bisexual Men in Spain and Portugal. (September 2020) - Pereira, Henrique; de Vries, Brian; Serrano, Juan Pedro; Afonso, Rosa Marina; Esgalhado, Graça; Monteiro, Samuel
The purpose of this study was to assess levels of depressive symptoms and quality of life in older gay and bisexual older Spanish and Portuguese men and explore associations between these two samples and these variables. Using online surveys, 191 older gay and bisexual men from Spain and Portugal (mean age = 70 years) completed the Spanish and Portuguese versions of the Center for Epidemiologic Studies—Depression Scale and World Health Organization Instrument to Assess Quality of Life. Overall, moderate levels of depression and quality of life were found. Gay men and Spanish men report higher levels of depressive symptoms than bisexual and Portuguese men. Gay men score higher on physical health dimensions; bisexual men score higher on the social relationships dimension. Lower levels of physical health, psychological symptoms, and social relationships were significant predictors of depressive symptoms. These exploratory findings offer both similarities and differences between the samples from the two countries—and with U.S. data—and further evidence of the pervasive experience of depression in the lives of sexual minority older men with a renewed awareness of myriad contexts within which individuals age.